Isolation and Characterization of Deltamethrin-Resistant Bacteria Isolated From Soil Originating From A Pepper Plantation - Oliver Swenson, Ragib (Universiti Malaysia Sarawak, UNIMAS, 2010)
Sixteen bacterial strains were isolated from soil taken from a pepper plantation that have the history of deltamethrin application were analyzed. Five Gram-negative, rod strains were assessed for resistance profile against the ascending deltamethrin concentration and all strains were putatively identified to five different genera include Acetobacter spp., Pseudomonas spp., Acidiphilium spp., Aminobacter spp. and Aeromonas spp. Aminobacter spp. was identified as the prolific deltamethrin-tolerant bacteria among five strains, which is able to tolerate deltamethrin with concentration up to 9600 ppm. The multi-resistant ability of isolates was further assessed with the testing the tolerance of these bacteria toward three heavy metals, mercury, copper and zinc. All five isolate showed tolerance to at least one heavy metal, which is copper. Aminobacter spp. showed resistance toward all three heavy metals, which proved to be a suitable candidate for biodegrader in co-contaminated soil environment. No plasmid was detected in all five isolates. Therefore it is believed that the resistance ability of isolates toward deltamethrin and some heavy metals are chromosomal encoded enzymatic reaction.